0519 Mindfulness Based Therapy for Insomnia Improves Objective Markers of Sleep in the Elderly: Preliminary Data from the Mindfulness Sleep Therapy (MIST) Study. (27th May 2020) - Wong, K F; Perini, F; Henderson, S L; Teng, J; Hassirim, Z; Lin, J; Leow, Z; Fan, Q; Ong, J; Lo, J; Ong, J C; Doshi, K; et al.
Abstract: Introduction: Mindfulness-based treatment for insomnia (MBTI) is a viable intervention for improving poor sleep. We report preliminary data from an ongoing pre-registered, randomized controlled trial which investigates the effect of MBTI on elderly adults. Methods: Participants above 50 years old with PSQI ≥ 5 were recruited and randomised into either MBTI or an active control group (Sleep hygiene education and exercise program, SHEEP) in sequential cohorts with about 20 participants per cohort (10 per group). Before and after the intervention, 1 night of portable polysomnography (PSG) and 1 week of actigraphy (ACT) and sleep diary (DIARY) data were collected. We report the ACT and DIARY results of the first 3 cohorts (n = 46, male = 23, mean age = 62.3, std = 6.3) and PSG data of the first 2 cohorts (n = 29, male = 12, mean age = 62.5, std = 5.7). Time in bed (TIB), total sleep time (TST), sleep onset latency (SOL), wake after sleep onset (WASO), and sleep efficiency (SE) were analysed with mixed-model repeated-measures ANOVA. Results: We observed increases in TIBDIARY (F1, 44 = 5.151, p < .05) and SEDIARY (F1, 44 = 22.633, p < .0001), and significant reductions in SOLDIARY (F1, 44 = 7.031, p < .05) and WASODIARY (F1, 39 = 7.411, p < .05). In the actigraphy data, we found a significant interaction in SOLACT (F1, 39 = 4.273, p < .05) with an increase in SHEEP SOLACT ( t 18 = 2.36, p < .05). Significant reductions were also observed in WASOACT (F1, 44 = 16.459, p < .0001) Finally, we observed a reduction in SOLPSG (F1, 26 = 5.037, p <. 05). All other tests were non-significant. Conclusion: Preliminary results suggest that both interventions lead to improvements in sleep with more pronounced effects in subjective sleep reports. Objective sleep data suggest that improvements in sleep is a result of improved sleep quality and not simply extending sleep opportunity. These preliminary data shows that MBTI may be a promising intervention for elderly individuals with sleep difficulties. Support: This study was supported by an award from the 7 th grant call of the Singapore Millennium Foundation Research Grant Programme